Managing the challenges in human service organizations a casebook - Austin, Michael J.; Brody, Ralph; Packard, Thomas Roy.; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2009)
Specialising in decisions managers need to make under trying circumstances, this casebook prepares current and aspiring managers for the kinds of experiences they are likely to encounter. The cases are inspired by real situations.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Human services -- Management; Electronic books